Optimized Implementation of Dijkstra’s Algorithm for Efficient Shortest Path Finding in Networked Systems - Narnavre, Siddhesh (International journal for research in applied science and engineering technology, 2024)
Dijkstra’s Algorithm, a popular answer based graph-based fully objective shortcut search, plays an important role in various communication systems and optimization problems These rules are important in packages of IoT networks, smart website online visitors management, and telecommunications, of which green-tracking and real-time priority-making are paramount In this paper, we discover now not most effective the classical software of Dijkstra’s Algorithm but additionally introduce optimizations that beautify its performance in largescale dynamic systems. [1] By tailoring the algorithm for particular contexts, including real-time records streams in IoT or adaptive routing in clever towns, we reveal sizeable enhancements in each computational overall performance and aid allocation. Our outcomes highlight the set of rules’s capability to evolve to modern challenges, ensuring quicker, greater accurate decisionmaking throughout numerous industries. The proposed upgrades open the door to further packages in future shrewd networks, offering solutions that might pressure improvements in self sufficient structures and scalable infrastructures. [2]